The cost-effectiveness of PHQ screening and collaborative care for depression in New York City - Jiao, Boshen (PLoS One, 2017)
BACKGROUND: Depression is under-diagnosed and under-treated in most areas of the US. New York City is currently looking to close gaps in identifying and treating depression through the adoption of a screening and collaborative care model deployed throughout the city. METHODS: We examine the cost-effectiveness of universal two-stage screening with the 2- and 9-item Patient Health Questionnaires (PHQ-2 and PHQ-9) in New York City followed by collaborative care for those who screen positive. We conducted microsimulations on hypothetical adult participants between ages 20 and 70. RESULTS: The incremental cost-effectiveness of the interventions over the average lifespan of a 20-year-old adult in NYC is approximately $1,726/QALY gained (95% plausible interval: cost-saving, $10,594/QALY gained). CONCLUSIONS: Two-stage screening coupled with collaborative care for depression in the clinical setting appears to be significantly less expensive than most clinical preventive interventions, such as HIV screening in high-risk patients. However, effectiveness is dependent on the city’s ability to manage scale up of collaborative care models.